Implications for Legal Certainty of Incorporating Blockchain Into the Documentation of Customary Law Institution Decisions - Yusuf, Darmawan; Pelawi, Jhon Tyson (PALAR (Pakuan Law review), 2025)
The development of blockchain technology opens up new opportunities in the digitization of legal documents, including decisions of customary institutions which have previously been documented conventionally and are vulnerable to loss, forgery, and discrepancies in recording. This study aims to analyze the potential for blockchain integration into customary law institutions' decision documentation systems and its implications for increasing legal certainty for indigenous communities and other stakeholders. The research method used is normative juridical, with legislative, conceptual, and comparative approaches, supported by secondary data in the form of literature related to blockchain, customary law, and legal certainty. The research results show that blockchain characteristics such as immutability, transparency, and decentralization can strengthen the authenticity and reliability of customary ruling documentation, making them more secure, permanent, and easily verifiable instruments. This technological integration also has the potential to clarify the position of customary rulings within the national legal system by improving documentation standards and facilitating the presentation of evidence before state institutions. However, blockchain implementation faces challenges such as digital infrastructure readiness, technological literacy among indigenous communities, and the need for regulatory harmonization, particularly regarding data protection, recognition of indigenous communities, and the validity of electronic evidence.